Development of Bilingual Pop Up Book Media on Javanese Puppet Stories for Elementary School Students - Wahyu Dinil Mustaqim; Arda Purnama Putra; Tri Murti (Universitas Negeri Malang, 2021)
This research and development aim to develop bilingual pop-up book media on Javanese puppet stories that valid according to the material experts, media experts, and teachers, as well as practical students. The research uses an ADDIE model with 5 stages, that is analysis, design, development, implementation, and evaluation. The results of validation by the material expert, media expert, and by the user (teacher) sequentially get a percentage of 96.4; 100; and 95.4 percent. While the result of the practicality test on the small scale test and the large scale test got a percentage of 93.3 and 97.5 percent. Media is categorized as very valid and very practical and can be used for elementary school students.